Literacy Habituation Program in Developing Reading Skills for Students with Intellectual Barriers at SMPKh Level - Pratama, Toni Yudha; Az-zahra, Afifah Sarah; Rasnah, Karlina Dieka; Salsabiil, Dhea Salmaa; Harits, Achmadi Fajar; Maharani, Ferina Agnis; Nursabrina, Putri Mayunda (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
The literacy habituation program aims to develop the reading skills of students with intellectual disabilities at the SMPKh level. This research focuses on the implementation of a literacy program specifically designed to meet the needs of students who experience difficulties in reading. Through an inclusive approach, this program not only improves reading skills, but also builds students' self-confidence and motivation. This research uses a qualitative method with a case study approach. Data was collected through observation, interviews with teachers and students, as well as analysis of documents related to literacy programs. The research results show that structured reading activities, such as reading together and using reading materials appropriate to students' level of understanding, are very effective in improving reading skills. Students show significant improvements in reading skills after participating in the program for one semester. The literacy habituation program has proven to be effective in improving reading skills for students with intellectual disabilities. It is hoped that this program can become a model for other schools in efforts to improve literacy skills among students with special needs.